Implications of AI on Cardiovascular Patients’ Routine Monitoring and Telemedicine - Arbaz Haider Khan; Hira Zainab; Roman Khan; Hafiz Khawar Hussain (CV. Multi Kreasi Media, 2024)
Cardiovascular and chronic disease management and treatment are started to incorporate Artificial Intelligence gradually into cardiovascular telemedicine and remote monitoring. Through the use of AI technologies, patients are much benefited, and at the same time, it promotes improvement in patients, examination, and continuous monitoring. Since the use of AI forefront in its role as a monitoring technique, predictive analytics, risk factors and detail personal medication in zone of cardio vascular diseases, this paper dwells on one how cardio vascular care is evolving with experimental use of AI. It also describes the limitation and challenge of AI use, for instance, around data privacy, legal regime and data quality, and AI moral decisions such as the disposition of openness and trust. Nevertheless, the current demands require future development in cardiology –telemedicine with the use of artificial intelligence in prescriptive and predictive cardiology based on precision medicine, machine learning, and genomic as well as electronic health records data. Therefore, the following aspects should be addressed to overcome the present challenges to the effective functioning of AI in the healthcare segment of cybersecurity threats, data connections, and accessibility. Therefore, the paper’s conclusion about the subject AI obversive points to the potential for a full-scale revolution in the sphere of cardiovascular care with regards to the patient’s outcomes and accessibility and effectiveness on the international level under conditions of further regulation as well as technological enhancement.